Exploring previous studies related to teacher competence, health risks, individual education plans and the development of students with special education needs visual impairment - Mohd Norazmi Nordin; Habibah Artini Ramlie; Norwaliza Abdul Wahab; Shaliza Alwi; Nor Fauziyana Mosbiran (Islamic Azad University, 2024)
The study aims to study the mastery of teachers in the implementation of Higher Level Thinking Skills (HTH) pedagogy in terms of knowledge, skills and teaching practices as well as their relationship with MBPK teaching planning. A total of 76 respondents from six schools around Batu Pahat were used as respondents through the distribution of questionnaires. The findings of the study show that teachers' knowledge in the implementation of KBAT is very important in planning lessons for MBPK. Studies identify the influence of teachers' teaching competence on their ability to plan good lessons for MBPK individuals. A set of questionnaires was used in this quantitative study for the purpose of data collection. The study involving these secondary school teachers was then analyzed using SEM with a focus on the formation of measurement models and structural models. Findings show that teacher competence has a significant influence on their teaching planning.